Diagnosis and management of de novo non-specific spinal infections: European Association of Neurosurgical Societies (EANS) Spine Section Delphi consensus recommendations - Andreas Kramer; Santhosh G. Thavarajasingam; Jonathan Neuhoff; Benjamin Davies; Giuseppe Barbagallo; Bertrand Debono; Bart Depreitere; Sven O. Eicker; Nikolay Gabrovsky; Marisa L. Gandia-Gonzalez; Marcel Ivanov; Radek Kaiser; et al. (Brain and Spine)
Introduction: The management of de novo non-specific spinal infections (spondylodiscitis - SD) remains inconsistent due to varying clinical practices and a lack of high-level evidence, particularly regarding the indications for surgery. Research question: This study aims to develop consensus recommendations for the diagnosis and management of SD, addressing diagnostic modalities, surgical indications, and treatment strategies. Material and methods: A Delphi process was conducted with 26 experts from the European Association of Neurosurgical Societies (EANS). Sixtytwo statements were developed on diagnostic workup, management decisions, surgical techniques, non-surgical treatment, and follow-up and submitted to the panel of experts. Results: Consensus was reached on 38 of 62 statements. MRI was confirmed as the gold standard for diagnosis. Regarding surgical indications, the panel agreed that any new neurological deficit, even subtle, warrants surgical consideration. Motor deficits with a motor score (MRC) below 4 and bladder or bowel dysfunction were unanimously considered clear indications for surgery. For spinal deformity and instability, thresholds such as kyphosis >20°, scoliosis >10°, and vertebral body collapse >50% were established to guide surgical decision-making. Minimally invasive surgery (MIS) was endorsed whenever feasible, and a 12 week antibiotic treatment regimen was favored in cases of complicated infections. Discussion and conclusion: This EANS consensus provides updated recommendations for SD management, incorporating recent evidence on improved outcomes with surgical therapy. While these guidelines offer a more structured approach to clinical decision-making, further research is required to optimize surgical timing and validate the long-term impact of these treatment strategies.